IKRAH (PAKSAAN) DALAM PERSPEKTIF HUKUM ISLAM - Mahmudin Mahmudin (STAI AL FALAH Banjarbaru, 2020)
In the perspective of Islamic Law, there is a provision whereby a person is allowed to do a prohibited act that is justified by sharia, one of which is ikrah, there are many Islamic laws related to ikrah and its division, maudu' about ikrah is one of the reasons for leniency in Islamic law, ikrah (forced circumstances) that is a person who is forced to do an act that he does not serve or likes. All these actions are done solely to protect himself from the force, which will result in danger to his safety or his limbs. Keywords: Coercion, Islamic Law